Does promotion and islamic business ethics increase consumer loyalty? empirical evidence Resto Kampoeng Banyumili Salatiga - Sigid Sardiyanto (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2019)
This research was a quantitative research that aimed to find out how the influence of promotion and Islamic business ethics on consumer loyalty in Kampung Banyumili Resto Salatiga. The analysis of the research was use Structural Equation Modeling (SEM).The results showed that promotion did not directly affect consumer loyalty, but it had a significant influence on buying interest. The buying interest had a significant influence on purchasing decision and it had a significant influence on fulfilling expectation. While the fulfilling expectation significantly effected on satisfaction and on customer loyalty, whereas Islamic business ethics had a significant effect on consumer loyalty. This study concluded that promotion did not directly affect consumer loyalty but passed buying interest, purchasing decision, fulfilling expectation, satisfaction and new customer loyalty.